MODEL EXPLICIT INSTRUCTION PADA PEMBUATAN CILOK SEHAT TERHADAP KETERAMPILAN VOKASIONAL BAGI ANAK TUNAGRAHITA RINGAN - PASA PANCAR RANI, AMALIA; WIJIASTUTI, ASRI (Jurnal Pendidikan Khusus, 2019)
The ability of mentally retardation children in mastering the influence of Explicit Instruction model in making healthy cilok toward vocational skill was still difficult so it influenced the learning ability which was less satisfied with the average value 54 or under KKM value. This research had purpose to apply the Explicit Instruction model in making healthy cilok toward vocational skill for mild mentally retardation children in SLB AC Dharma Wanita Sidoarjo. This research used quantitative of pre experiment kind with One Group Pre test ? Post Test design. The research result indicated that the average pre test showed value, 54. A student got the lowest value, 48 while the highest value was 60. The treatment was implemented for 6 times meeting with the student?s success level in making healthy cilok with Explicit Instruction model numbered 6 students who could do the learning activity. The research finding of the average post test result showed value, 83. The student got the lowest value, 77 while the highest value was 88. The researcher?s conclusion stated that the Explicit Instruction model in making healthy cilok had significant influence to Explicit Instruction model toward making healthy cilok to vocational skill for mild mentally retardation children in SLB AC Dharma Wanita Sidoarjo. So, the Zh value, 2,52 was greater than critic value Z table = 1,96, ? = 5%. Keywords: Explicit Instruction model, vocational skill, making healthy cilok, mild mentally retardation children